Perbandingan Model Karakteristik Arus Lalu Lintas Dengan Model Greenshields, Greenberg dan Underwood Pada Ruas Jalan Kaharuddin Nasution - Ester Febiola; Rizqy Ridho Prakasa; Mardani Sebayang; Sri Djuniati (Sekolah Tinggi Teknologi Pekanbaru, 2026)
The growth of population and vehicles in the city of Pekanbaru increases traffic flow, especially on Jalan Kaharuddin Nasution which has high activity. This condition causes a decrease in road performance with category E service levels. This study aims to analyze the characteristics of traffic flow on the Kaharuddin Nasution Road section using Greenshields, Greenberg, and Underwood models. The research method is in the form of a field survey which includes observation of traffic volume, side obstacles, and vehicle speed. In addition, linear regression analysis was carried out to determine the relationship between volume, speed, and density. The results of the study conducted on Thursday showed that the relationship between volume, speed, and density based on each model have different levels of suitability with the field data. Based on the highest coefficient of determination, the model that most dominantly represents traffic flow characteristics on Jalan Kaharuddin Nasution is the Greenberg model. For the southbound direction, the Speed–Density (S–D) relationship yields an R² value of 0.7991 with the equation S=67,66 – 9,39LnD. The Volume–Density (V–D) relationship yields an R² value of 0.9471 with the equation V=67,66D – 9,39DLnD. The Volume–Speed (V–S) relationship yields an R² value of 0.4730 with the equation V=1.348,24.S.e^(-S/9,39) For the northbound direction, the Speed–Density (S–D) relationship yields an R² value of 0.1317 with the equation S=55,30 – 4,35LnD. The Volume–Density (V–D) relationship yields an R² value of 0.9099 with the equation V=55,30D – 4,35DLnD. The Volume–Speed (V–S) relationship yields an R² value of 0.00003 with the equation V=334.243,05.S.e^(-S/4,35)